On the measure of power and the power of measure in international relations - Stefano Guzzini (Danish Institute for International Studies (DIIS), 2009)
Under the Bush administration, the US portrayed itself as a necessary Empire. 'Given its extraordinary power, the US has a special responsibility to intervene in world politics and can be exempted of the usual constraints put on such interventions.' The present Working Paper analyses the role of the concept of power in such explanations. Its first claim is that these explanations must tacitly or overtly assume that power can be measured and that, however, such measurement of power is not possible. Secondly, it shows that instead of neutrally registering a distribution of power, measures of power intervene into actual power politics. Power is conceptually tied to the idea of responsibility ('ought implies can') in our political discourse. Hence, attributing power to actors requires of them to justify their action or non-action. Inversely, a claim to have superior power enables a claim to special responsibilities. The paper illustrates such interactive effects by discussing the present debate about US power, in particular the alleged unipolarity of the system and the idea of a US Empire. It shows, that the way we conceive of power, if it becomes shared, accompanies and legitimates certain foreign policy action.
Keywords: 330; Internationale Beziehungen; Macht